(secA-tanA)^2=1-sinA/1+sinA
Answers
Answered by
1
Answer:
Above photo will give you your answer
Attachments:
![](https://hi-static.z-dn.net/files/d6d/a10699d513b21d174bb200b21ea16391.jpg)
Answered by
0
Answer:
Step-by-step explanation:
(secA-tanA)^2=1-sin/1+sin
(secA-tanA)^2=1-sin/1+sin*1-sin/1+sin rationalise it
(secA-tanA)^2=1+sin^2-2sin/1-sin^2
(secA-tanA)^2=1+sin^2-2sin/cos^2
(secA-tanA)^2=1/cos^2 +sin^2/cos^2-2sin/cos^2
(secA-tanA)^2=sec^2+tan^2-2sesctanA
(secA-tanA)^2=(secA-tanA)^2
LHS=RHS
PROVED
HOPE ITS HELPFULL
MARK ME AS BRAINLIEST
Similar questions